Organic fertilizer applications improve the growth of vegetable crops and chemical properties in the tailings deposition area at Timika, Papua, Indonesia - SARTJI Taberima; Saraswati Prabawardani; ROBERTH SARWOM; Graham Lyons (Nusantara Bioscience, 2020)
Abstract. Taberima S, Prabawardani S, Sarwom R, Lyons G. 2020. Organic fertilizer applications improve the growth of vegetable crops and chemical properties in the tailings deposition area at Timika, Papua, Indonesia. Nusantara Bioscience 12: 134-142. This study aimed to observe growth responses of selected vegetable crops grown in the media of inactive tailings, the available nutrients (macro and microelements) in fresh tailings before and after planting, as well as the metal uptake by plant tissues. Research was conducted using Randomized Block Design with three treatments of organic matter (chicken manure, cow manure, and compost of Salvinia natans) to observe the response on growth and yield of kangkong, red spinach, tomato, and chili. Based on the geochemical data, the ratio of ANC/MPA ranged from 3.81 (0-20 cm) to 4.60 (20-40 cm). There was no acid potential, with ANC ratio > 1.5 x MPA, and this result was supported by soil pH, which was alkaline in both depths of tailings media, ranging from 7.94 (0-20 cm) to 7.90 (20-40 cm). There was no significant effect on the chemical properties in the first period before and after planting for three months of planting period, except for the application with organic fertilizers. The best organic fertilizers applied in fresh tailings were chicken manure, followed by the compost of S. natans and cow manure. These organic fertilizers produced good growth and yield components of kangkong, red spinach, tomato, and chili. Meanwhile, the lowest growth and yield response of these crops was shown by control (without compost or manure). The level of metal uptake by all vegetables was low, suggesting that these vegetables are safe to be consumed.